Recent advances in catalytic CO2 reduction by organometal complexes anchored on modified electrodes. (8th March 2016) - Sun, Cunfa; Gobetto, Roberto; Nervi, Carlo
Abstract : A critical overview of the very recent literature on heterogeneous electrochemical catalysis of CO2 reduction with organic metal modified electrodes is summarized by taking into account different functionalization methods. Abstract : A critical overview of the very recent literature on heterogeneous electrochemical catalysis of CO2 reduction with organic metal modified electrodes is summarized. Five methods for electrode funtionalization are discussed and compared in terms of efficiency and selectivity: adsorption, by using membranes, adopting a "hybrid" covalent organic framework approach, performing electropolymerization directly on the electrode surface, and exploiting the formation of strong covalent chemical bonds between the surface and the desired catalyst.